Law Enforcement Against Defamation Perpetrators Through Instagram Social Media - Nur Hidayah; Annisa Larasati Simanjuntak (Program Pascasarjana UIN Sumatera Utara Medan, 2019)
The rapid development of information and communication technology has significantly influenced social interaction and public communication through digital platforms, including social media such as Instagram. While technological advancement provides many benefits, it also creates opportunities for misuse, including defamation and insults committed through electronic media. Defamation on social media can harm a person’s honor, reputation, and psychological well-being, making it an important legal issue in Indonesia. This study aims to analyze the implementation of criminal sanctions against perpetrators of defamation through Instagram, identify factors inhibiting law enforcement, and examine legal protection provided to victims. This research uses a normative juridical approach with qualitative methods through literature studies by analyzing legislation, legal materials, and court decisions related to defamation and electronic information. The results show that criminal sanctions for defamation through social media are regulated under Article 27 paragraph (3) of the Electronic Information and Transactions Law and several provisions of the Criminal Code concerning defamation and slander. However, the enforcement of these regulations remains constrained by weak law enforcement, limited facilities, inadequate public legal awareness, and challenges in cybercrime investigations. Victims of defamation are entitled to legal protection through complaint mechanisms, witness and victim protection institutions, and content removal procedures within electronic systems. Therefore, stronger law enforcement, improved digital literacy, enhanced cyber investigation capacity, and greater public awareness are necessary to reduce cases of online defamation and ensure legal protection for victims in Indonesia’s digital environment.